E-WOM: Pengaruh Intensity, Valence of Opinion, dan Content Terhadap Keputusan Pembelian Jasa pada Allegra Dance School dengan Brand Trust sebagai Variabel Moderasi - Natasha, Jennifer; Rozaq , Muhammad Kholid Arif (Syntax Literate, 2025)
The Indonesian National Police (Polri) as a law enforcement institution faces complex challenges in this modern era. The strategic position of the National Police in the Indonesian constitutional system places this institution at the crossroads between the demands of professionalism, independence, and public accountability. Contemporary political dynamics and changes in institutional image have a significant impact on the existence and legitimacy of the National Police in the eyes of the public. The National Police of the Republic of Indonesia (Polri) is faced with the dynamics of political disruption and the challenge of maintaining the image of the institution in the contemporary era. A comprehensive analysis identified that the existence of the National Police was influenced by three main factors: (1) the dynamics of the democratic transition that resulted in the separation of the institution from the TNI, (2) political intervention in police operations, and (3) fluctuations in public trust in institutional performance. An analysis that covers various aspects ranging from post-reform institutional transformation, the impact of political disruption, institutional image problems, to future strengthening strategies shows that the National Police faces an institutional dilemma between maintaining professionalism and the pressure of political interests. As an implication, the National Police needs to develop adaptive strategies to strengthen institutional independence, increase operational transparency, and build effective accountability mechanisms. This research contributes to the discourse of police reform in the context of consolidating democracy in Indonesia.